2017
DOI: 10.1186/s13049-017-0399-4
|View full text |Cite
|
Sign up to set email alerts
|

Poor performance of quick-SOFA (qSOFA) score in predicting severe sepsis and mortality – a prospective study of patients admitted with infection to the emergency department

Abstract: BackgroundWe aimed to evaluate the clinical usefulness of qSOFA as a risk stratification tool for patients admitted with infection compared to traditional SIRS criteria or our triage system; the Rapid Emergency Triage and Treatment System (RETTS).MethodsThe study was an observational cohort study performed at one Emergency Department (ED) in an urban university teaching hospital in Norway, with approximately 20,000 visits per year. All patients >16 years presenting with symptoms or clinical signs suggesting an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
156
6
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 214 publications
(182 citation statements)
references
References 22 publications
14
156
6
6
Order By: Relevance
“…On a merged dataset of 12 555 patients from multiple EDs in Australia and The Netherlands, post hoc addition of lactate ≥2 mmol/L cut‐off to the qSOFA score resulted in improved sensitivity for identifying patients at risk for mortality or prolonged ICU stay. Our study found poor sensitivity for the qSOFA score, which is in keeping with recent prospective evaluations …”
Section: Discussionsupporting
confidence: 92%
“…On a merged dataset of 12 555 patients from multiple EDs in Australia and The Netherlands, post hoc addition of lactate ≥2 mmol/L cut‐off to the qSOFA score resulted in improved sensitivity for identifying patients at risk for mortality or prolonged ICU stay. Our study found poor sensitivity for the qSOFA score, which is in keeping with recent prospective evaluations …”
Section: Discussionsupporting
confidence: 92%
“…Askim et al showed that a SIRS score of≥2 had higher sensitivity than qSOFA in predicting both 7-day and 30-day mortality (15). In addition, our findings supported (75.4%) this argument.…”
Section: Discussionsupporting
confidence: 85%
“…The qSOFA score should provide a simple bedside score to identify adult patients outside the ICU with suspected infection who are likely to have poor outcomes, and an increased qSOFA should prompt clinicians to further investigate for organ dysfunction, to initiate or escalate therapy as appropriate, and to consider referral to critical care or increase the frequency of monitoring. However, we and others have shown that qSOFA does not perform well in identifying and prognosticating critical illness and sepsis in the emergency room (ER) 4. It is therefore an urgent need of prospective studies on the usefulness of qSOFA in clinical settings outside the ICU (ie, in prehospital setting, ER and at the ward).…”
Section: Commentarymentioning
confidence: 99%